The combination of salt and drought benefits selective ion absorption and nutrient use efficiency of halophyte Panicum antidotale - Hussain, Tabassum; Asrar, Hina; Zhang, Wensheng; Liu, Xiaojing (Frontiers in Plant Science, 2023)
Soil salinity and water deficit often occur concurrently, but understanding their combined effects on plants’ ion regulation is limited. With aim to identify if introducing drought with salinity alleviates salt stress’s ionic effects, Panicum antidotale – a halophytic grass- was grown in the presence of single and combined stressors, i.e., drought and salt (low and high). Regulation of cations and anions along with the antioxidant capacity and modifications in leaf anatomy were investigated. Results showed a combination of low salt and drought minimally affected plant (dry) mass by improving the selective ions absorption and nutrient use efficiencies. The lowest ratio for efficiency of photosystem II and carbon assimilation (ΦPSII/ΦCO2) suggested less generation of reactive oxygen species, which were probably detoxified with constitutively performing antioxidant enzymes. In contrast, the combination of high salinity and drought escalated the adverse effects caused due to individual stressors. The selective ion absorption increased, but the non-selective ions transport caused an ionic imbalance indicating the highest ratio of Na+/K+. Although the area of mesophyll increased, a reduction in epidermis (cell number and area) predicted a mechanical injury prone to water loss in these plants. The compromised activity of antioxidant enzymes also suggested treatment-induced oxidative damage. Yet, the synergistic interaction between high salinity and drought was not detrimental to the survival of P. antidotale. Therefore, we suggest planting this grass in habitats with harsh environmental conditions to meet the increasing fodder demands without compromising agricultural lands’ productivity.